1998
DOI: 10.1021/bi980945h
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of the N-Terminal Region of the Lon Protease from Mycobacterium smegmatis

Abstract: Lon protease homologues contain a poorly conserved N-terminal region of variable length. To better understand the role of the N-terminal region of Lon in the complicated reaction cycle of ATP-dependent protein degradation, we expressed and characterized mutants of the Lon protease from Mycobacterium smegmatis (Ms-Lon) lacking 90, 225, and 277 N-terminal residues (N-G91, N-E226, and N-I278, respectively). N-I278 displayed neither peptidase nor ATPase activity despite the fact that it was stable and soluble in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 41 publications
3
47
0
Order By: Relevance
“…At sufficiently high concentrations, such inhibitors fill most sites and prevent substrate binding. Previous studies also showed that protein substrates activate ATP-independent Lon cleavage of very small peptide mimics (14,7). Evidence for two conformations of Lon, whose populations change as a function of substrate binding, was obtained by assaying degradation and ATP hydrolysis under identical conditions as a function of titin-I27 CM -␤20 concentration (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…At sufficiently high concentrations, such inhibitors fill most sites and prevent substrate binding. Previous studies also showed that protein substrates activate ATP-independent Lon cleavage of very small peptide mimics (14,7). Evidence for two conformations of Lon, whose populations change as a function of substrate binding, was obtained by assaying degradation and ATP hydrolysis under identical conditions as a function of titin-I27 CM -␤20 concentration (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…This model also accounts for the stimulation of Lon degradation of one substrate by another substrate and for previous reports that proteins substrates stimulate Lon peptidase activity (7,14).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…To demonstrate the protease activity of purified Lon, casein covalently labeled with fluorescein isothiocyanate (FITC-casein) was used as a substrate (46,47,49). The energy-dependent degradation of casein has been routinely employed to characterize bacterial, yeast, and mammalian Lon (1,8,46,50).…”
Section: Purification Of Recombinant Human Lon and Analysis Of Itsmentioning
confidence: 99%